Application of Dual-Source-Computed Tomography in Pediatric Cardiology in Children Within the First Year of Life - Hausmann, P.; Stenger, A.; Dittrich, S.; Cesnjevar, R.; Rüffer, A.; Hammon, M.; Uder, M.; Rompel, O.; Glöckler, M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2016)
Purpose: To assess fields of application and value of dual source computed tomography (DSCT) for diagnostics and therapy in patients with congenital heart disease during their first year of life. Evaluation of image quality, surgical use and radiation exposure of 2nd and 3 rd generation DSCT.Materials and methods: DSCT was applied in 118 cases between January 2012 and October 2014 for diagnostics of congenital heart defects. 2nd generation was used in 91 cases until April 2014 and 3 rd generation in 27 cases during the period thereafter. 3 D reconstructions of the image data were created for clinical diagnostics and planning of interventions. Image quality was assessed using a 4-point-scale. The visibility of the mammary arteries was analyzed, and signal-to-noise-ratio (SNR) and contrast-to-noise-ratio (CNR) were calculated. The usefulness of 3D-reconstructions for surgical planning was rated using a 5-point-scale. Radiation exposure and contrast dye consumption were determined. All cases were analyzed retrospectively.Results: DSCT was successfully used in 118 cases. All image data obtained were interpretable. More than 60 percent of cases did not show any artifacts. The mammary arteries were visible down to the diaphragmatic arch in more than 80 percent of cases. Diagnostic value and surgical benefit were evaluated as “useful” or as “essential” in all cases. Median radiation dose was 0.4 mSv and 0.27 mSv for the 2nd and 3 rd generation DSCT, respectively. Consumption of contrast dye was 2 ml/kg in all cases.Conclusion: DSCT is a modern and extremely helpful technique for diagnostics and planning of interventions in patients with complex congenital heart defects. Extracardiac vascular structures in particular can be depicted three-dimensionally at high resolution. The use of iterative reconstruction with 3 rd generation DSCT yielded image quality similar to that of 2nd generation DSCT at considerably reduced radiation exposure level compared to 2nd generation DSCT. 3 rd generation DSCT is a low risk, accurate and extremely fast technique for diagnosing unstable patients with CHD.Key points:• Expanded scope of indications for DSCT in diagnosing critically ill infants• Effective radiation dose is considerably lower than 0.5 mSv• Extremely rapid image acquisitions with high image quality• Possibility of optimized 3D-based surgical planningCitation Format:• Hausmann P, Stenger A, Dittrich S et al. Application of Dual-Source-Computed Tomography in Pediatric Cardiology in Children Within the First Year of Life. Fortschr Röntgenstr 2016; 188: 179 – 187
Keywords: heart; CT-angiography; surgery